Globus Pallidus Interna and Ventral Intermediate Nucleus of the Thalamus Deep Brain Stimulation for Adductor Laryngeal Dystonia: a Case Report of Blinded Analyses of Objective Voice Outcomes in 2 Patients. Issue 4 (11th April 2022) - Patel, Rita R.; Zauber, S. Elizabeth; Yadav, Amol P.; Witt, Thomas C.; Halum, Stacey; Gupta, Kunal
Abstract : BACKGROUND: Adductor laryngeal dystonia (ADLD) is a substantially debilitating focal progressive neurological voice disorder. Current standard of care is symptomatic treatment with repeated injections of botulinum toxin into specific intrinsic laryngeal muscles with extremely variable and temporary benefits. We report the use of bilateral deep brain stimulation (DBS) of globus pallidus (GPi) for long-term improvement of ADLD voice symptoms. OBJECTIVE: To investigate the effects of bilateral DBS of the GPi and ventral intermediate nucleus (VIM) of the thalamus on vocal function in 2 patients with ADLD associated with voice and hand tremor. METHODS: Blinded objective and quantitative analyses of voice were conducted before and after treatment in 2 female patients (70 and 69 years). Paired t -tests were conducted to compare voice measurements pre-GPi and post-GPi and VIM-DBS. A 2-way analysis of variance was conducted to determine the interaction between target (GPi/VIM) and time (pre/post) for each voice measure. RESULTS: Although the follow-up period differed between patients, the GPi-DBS implanted patient had notable improvement in vowel voicing (%), extent of tremor intensity (%), and overall speech intelligibility (%), compared with preoperative status. GPi-DBS also resulted in significant improvement in cepstral peak prominence (dB). VIM-DBS resulted in a significantly greater change in the tremor rate (Hz). CONCLUSION: Changes in phonatory function provide preliminary support for the use of bilateral GPi-DBS for treatment of ADLD and bilateral VIM-DBS for vocal tremor predominant ADLD. Future studies with larger sample sizes and standardized follow-up periods are needed to better assess the role of DBS for ADLD.